MODELING OF THE CLUSTER SYSTEM OF ADDITIONAL PROFESSIONAL EDUCATION IN CONDITIONS OF QUALITATIVE AND STRUCTURAL CHANGES IN THE ECONOMY OF THE SAKHA REPUBLIC (YAKUTIA) - Mikhailova, Evgenia; Chorosova, Olga; Solomonova, Galina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The process of implementing the cluster approach in education requires the awareness of its theoretical, methodological and applied aspects taking place in Russia. The basis of the cluster methodology in education is the consideration of forms of socio-economic relations aimed at creating a modern innovative products as an holistic set of elements in conjunction relations between them. The cluster approach needs the methodological basis of interdisciplinary processes, scientific and theoretical awareness of key tasks and strategic orientations in professional and additional professional education since the management theory of educational clusters, the regulation of establishment and functioning has not yet received proper development in regional conditions. The following methodological principles are used in the research of clusters and cluster systems: systematic approach for the research of economic development of the region considering the clusters and cluster systems of external and internal environment; use of the regional features of functioning; the feasibility of modeling activities results of cluster systems.The research aim is to develop a cluster system model of additional professional education at NEFU capable of meeting the needs of Yakutia by highly qualified personnel. Objectives: to analyze the conceptual field of the cluster system in the educational space of NEFU with regard to additional professional education; the comparative research of the clusters of the North-Eastern Federal University, the Sakha Republic (Yakutia) in assessing its activity and influence on innovative, technological and social development of the region etc.